Nanospiderwebs: Artificial 3D Extracellular Matrix from Nanofibers by Novel Clinical Grade Electrospinning for Stem Cell Delivery. Issue 5 (1st November 2012) - Alamein, Mohammad A.; Liu, Qin; Stephens, Sebastien; Skabo, Stuart; Warnke, Frauke; Bourke, Robert; Heiner, Peter; Warnke, Patrick H.
Abstract Novel clinical grade electrospinning methods could provide three‐dimensional (3D) nanostructured biomaterials comprising of synthetic or natural biopolymer nanofibers. Such advanced materials could potentially mimic the natural extracellular matrix (ECM) accurately and may provide superior niche‐like spaces on the subcellular scale for optimal stem‐cell attachment and individual cell homing in regenerative therapies. The goal of this study was to design several novel "nanofibrous extracellular matrices" (NF‐ECMs) with a natural mesh‐like 3D architecture through a unique needle‐free multi‐jet electrospinning method in highly controlled manner to comply with good manufacturing practices (GMP) for the production of advanced healthcare materials for regenerative medicine, and to test cellular behavior of human mesenchymal stem cells (HMSCs) on these. Biopolymers manufactured as 3D NF‐ECM meshes under clinical grade GMP‐like conditions show higher intrinsic cytobiocompatibility with superior cell integration and proliferation if compared to their 2D counterparts or a clinically‐approved collagen membrane.